2009
DOI: 10.1007/s00415-009-5420-z
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism in a population of northern Tanzania: a community-based door-to-door study in combination with a prospective hospital-based evaluation

Abstract: The prevalence of Parkinson's disease (PD) in sub-Saharan Africa is still a matter of debate. The few studies that have been conducted have shown prevalences lower than those in the western world. Whether this represents a genuine finding is unclear to date. In northern Tanzania, we have conducted a hospital-based evaluation and a community-based door-to-door study to assess the prevalence of Parkinsonism, including that of PD. Over a period of 8 months, all patients admitted to a mid-size rural hospital were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
0
9
2
Order By: Relevance
“…Of the 47 included studies, 21 were performed in Asia, 11 in Europe, 5 in Africa, 4 in Australia, 4 in South America, and 2 in North America (see Supplemental Data Table e‐1). Most studies used a two‐stage procedure to identify individuals with PD.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 included studies, 21 were performed in Asia, 11 in Europe, 5 in Africa, 4 in Australia, 4 in South America, and 2 in North America (see Supplemental Data Table e‐1). Most studies used a two‐stage procedure to identify individuals with PD.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 40-year-old American population, the risk of PD in men is about 2%, while in women is 1.3% [11]. The age-adjusted prevalence of PD reflects morbidity and mortality, which in Africa is lower than that in Europe, the United States, and Asia [12][13][14]. Currently, there are fewer morbidity data related to racial or ethnic, but the incidence varies according to the current research.…”
Section: Epidemiology Study Of Parkinson's Diseasementioning
confidence: 86%
“…Indian studies reported a high prevalence of epilepsy in 20.6% [ 13 ] while in rural Tanzania, the prevalence of epilepsy was 2.91/1000 adults [ 26 ] and 4.9% in a rural area of Bilomo in Cameroon [ 27 ]. Other studies in Sub-Saharan Africa have reported crude yearly stroke incidence rates of 94.5-107.9/100, 000 [ 17 ], 20/100,000 for Parkinson disease [ 28 ], 41/100,000 for essential tremor [ 29 ], 4.3% for 1-year prevalence of migraine headache [ 16 ], and 0.1% for hospital-based prevalence of Parkinsonism [ 30 ]. The classification of neurological diseases in the elderly in urban Africa is important in terms of diagnostic approach, therapy and prognosis.…”
Section: Discussionmentioning
confidence: 99%